The Coimbra See and its Chancery in Medieval Times - Morujão, Maria do Rosário Barbosa (2006)
This article seeks to resume the main conclusions of the author’s Ph.D. thesis on the Coimbra See as an institution and a chancery from 1080 to 1318. The institutional approach, examining the evolution of the history of the diocese and its bishops, the organisation of the chapter and the government of the diocese, establishes a context for the study of the cathedral chancery, seeking to discover not only the charters produced at that writing office and their composition, writing and practices of validation, but also the human side of the scribes who worked there.